Design Computing and Cognition '12 - Gero, John S. (Springer Netherlands : Imprint: Springer, 2014)
Design thinking, the label given to the acts of designing, has become a paradigmatic view that has transcended the discipline of design and is now widely used in business and elsewhere. As a consequence there is an increasing interest in design research. This is because of the realization that design is part of the wealth creation of a nation and needs to be better understood and taught. The continuing globalization of industry and trade has required nations to re-examine where their core contributions lie if not in production efficiency. Design is a precursor to manufacturing for physical objects and is the precursor to implementation for virtual objects. At the same time, the need for sustainable development requires the design of new products and processes, which feeds a movement towards design innovations and inventions. The papers in this volume are from the Fifth International Conference on Design Computing and Cognition (DCC'12) held at Texas A & M University, USA. They represent the state-of-the-art of research and development in design computing and design cognition. They are of particular interest to researchers, developers and users of advanced computation in design and those who need to gain a better understanding of designing.